Determination of Internal Structure of Semeru Volcano Based on Seismic Attenuation Imagery - Hena Dian Ayu; Adi Susilo; Sukir Maryanto; Muhamad Hendrasto (Natural B, Journal of Health and Environmental Sciences, 2013)
Characteristic of medium could be defined by physical parameters such as seismic velocity and attenuation. Amplitude, hyocentral distance, frequency and attenuation coefficient is required to determine the Q-factor value  or attenuation in effort on imaging the internal structure. In this study, we used volcanic earthquakes data of Semeru Volcano recorded 2009 that consist 54 seismogram (24 A-type volcanic earthquakes and 24 explosion volcanic earthquakes. The Q-factor value of A-type volcanic earthquakes is 4 - 392 or about 78,87 and the Q-factor value of explosion volcanic earthquakes is 4 - 288 or about 51,39. In term of the image quality, it can be seen that the attenuation on Jongring Seloko active caldera and under Jongring Seloko have low attenuation value or high Q-factor value thas was called the zone beneath. The zone beneath is interpreted to associated with hot material that may indicate the magma chamber that  concentrated in the depth interval of 1-1,8 km from the top of Semeru Volcano. The zone beneath have structural trends on West-East-Southeastern-South sector out the volcano. The internal structure of Semeru Volcano is predominance of sedimentary rocks, sandstone and rocks with gas in pore space. Although in some deep layer have internal structure as metamorphic rocks and igneous rock.